2006
DOI: 10.1002/cbf.1365
|View full text |Cite
|
Sign up to set email alerts
|

Acute exercise stimulates macrophage function: possible role of NF‐κB pathways

Abstract: Moderate physical activity when performed on a regular basis presents a number of benefits to the whole organism, especially regarding immune system function, such as augmenting resistance to infections and to cancer growth. Although glutamine production by active muscle cells as well as neuroendocrine alterations mediated by the chronic adaptation to exercise may play a role, the entire mechanism by which exercise makes the immune system aware of challenges remains mostly uncovered. This is particularly true … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
6

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 35 publications
0
44
0
6
Order By: Relevance
“…9,10 Exercise mobilizes peripheral immune cells and the magnitude of this effect reflects the intensity and duration of the effort. 11,12 Intense training increases the susceptibility to infections 9 and this may result from impairment in neutrophil function or acceleration in the process of neutrophil death. 13 Short-term exhaustive exercise or intensive treadmill exercise is known to induce DNA damage in lymphocytes in 14 Recently, we have demonstrated that a single session of exercise induces DNA fragmentation and mitochondrial membrane depolarization, increases expression of pro-apoptotic genes (bax and bcl-xS) and decreases expression of anti-apoptotic genes (bcl-xL) in rat neutrophils.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Exercise mobilizes peripheral immune cells and the magnitude of this effect reflects the intensity and duration of the effort. 11,12 Intense training increases the susceptibility to infections 9 and this may result from impairment in neutrophil function or acceleration in the process of neutrophil death. 13 Short-term exhaustive exercise or intensive treadmill exercise is known to induce DNA damage in lymphocytes in 14 Recently, we have demonstrated that a single session of exercise induces DNA fragmentation and mitochondrial membrane depolarization, increases expression of pro-apoptotic genes (bax and bcl-xS) and decreases expression of anti-apoptotic genes (bcl-xL) in rat neutrophils.…”
Section: Introductionmentioning
confidence: 99%
“…The response depends on the intensity, duration and mode of exercise, changes in body temperature, blood flow, hydration status and body position concentrations of hormones and cytokines. The cells showing more responsiveness to the effects of acute exercise, both in terms of numbers and function, are NK cells, neutrophils and macrophages [60]. Instead, helper T-cell counts and other immune measures are not enhanced significantly.…”
Section: Physical Activity and Immune Functionmentioning
confidence: 93%
“…Following that, physical exercise, which is the most powerful physiological inducer of iHSP70 expression, compared only to heat stress and fever-related conditions [34,[46][47][48], is considered, at the same time, the best solution to unfasten this perceived Gordian knot (an intractable problem that may be solved by "thinking outside the box") of senescence-associated chronic inflammatory diseases, as recently suggested [7]. In addition to that, several studies have reported that the amino acid L-glutamine (thereafter referred to as glutamine) strongly enhances the HS response by acting as a potentializer of iHSP70 expression [49,50], mainly via the hexosamine biosynthetic pathway (HBP) [51][52][53][54][55][56].…”
Section: Anti-misfolding Protein Quality Control Systemsmentioning
confidence: 99%